(untitled) (ICADE. Revista de la Facultad de Derecho, 2012)
Autores: Mercedes Gómez Adanero,Juan Antonio Gómez García,José Carlos Muinelo Cobo, JoséLuis Muñoz de Baena Simón Editorial: Universidad Nacional deEducación a Distancia, Madrid2006, 296 páginas